Simultaneous Estimation of Telmisartan and Hydrochlorothiazide in Tablet Dosage Form by HPTLC Method - MAHESWARI, R.; MAGESWARI, S.D.; SURENDRA, K.; GUNASEKARAN, V.; SHANMUGASUNDARAM, P. (Asian Journal of Chemistry, 2010)
A validated HPTLC method for simultaneous estimation of telmisartan and hydrochlorothiazide in tablet formulations is described. The separation was achieved on pre-coated silica gel plate 60 F254 using ethyl acetate:chloroform:methanol (10:3:1 v/v/v) as mobile phase. Quantification was carried out by the use of densitometer in absorbance mode at 270 nm. Linearity of detector response for telmisartan and hydrochlorothiazide estimated in the average weight of the tablet were found to be 39.58 and 12.48 mg, respectively. The percentage recovery of telmisartan and hydrochlorothiazide estimated in the average weight of the tablet were found to be 99.61 and 99.49 %, respectively. The proposed method is accurate, precise and reproducible and can be adopted for routine analysis of telmisartan and hydrochlorothiazide in tablet formulation.